Physicochemical, Major Anions and Heavy Metals in Surface Water and Groundwater at Pb – Zn Mining areas of Ebonyi State, Nigeria - SU Opoke; AD Osayande (Journal of Applied Sciences and Environmental Management)
This research is an Appraisal of Physicochemical, major anions and heavy in Surface Water and Groundwater at Pb – Zn Mining areas of Ebonyi state. Heavy metals in borehole samples were analysed using Atomic Absorption Spectrometer (AAS). Physico-chemical parameters determined. Its shows that pH is generally low (3.65) resulting from the dissolution of the sulphide Ore. The heavy metal mean trend indicates that Fe > Zn >Pb> Cr >Cu > Ni > AS > Cd in the water samples. Fe, Zn, Cu, Pb and Cr were observed to be high. The variations for the heavy metals suggest that mining operation is responsible for the distribution and redistribution of chemical elements. The result of the Correlation analysis and principal component analysis ( R- Mode and Q-mode) applied to the data analysis show that Zn, Pb, Cd, Cu, and Cr heavy metals originated from similar sources but may have been influenced by mining operation, while Ni, and As are attributed to a geogenic source. Proper sewage disposal practice and water conventional treatment strategies are recommended.